Determination of appropriate public transportation mode for UP-Philcoa route in accordance with the omnibus franchising guidelines - Frayna, Ana Marie S.; Ventura, Aliannah E.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
In line with the proposed modernization of the transportation system in the Philippines, new franchising guidelines of public utility vehicles are released and are stated in the Department Order No. 2017-011 of the Department of Transportation (DOTr). According to the said order, also known as Omnibus Franchising Guidelines (OFG), PUJs are "restricted from operating along EDSA and national highways or expressways in highly urbanized areas" (DOTr, 2017). Therefore, the UP-Philcoa, UP-North EDSA, and UPPantranco PUJS would be affected. Public Utility Buses (PUBs) and mini-buses are preferred to traverse along major transport corridors (DOTr, 2017), thus, Philcoa will serve as a transfer area for passengers that are going in and out of UP and there will no longer be direct trips from UP to SM North EDSA and MRT-3 Quezon Avenue, and vice versa. That is why for this study, the appropriate public transport mode/s that would operate along the consolidated UP-Philcoa route is/are determined, including the number of PUV units needed to accommodate the served demand of the said route. Two transport surveys were conducted to determine the served passenger demand for the UP-Philcoa route- Boarding and Alighting Survey and Public Transport Frequency Survey. As a result of this study, two options are proposed for the public transport mode to be used in the consolidated UP-Philcoa route - (1) Mini-bus, and (2) Public Utility Jeepney (PUJ). If mini-buses are to be considered for the said UP-Philcoa route, 75 units are needed to accommodate the total served demand of 10,789 passengers for the whole service period, where 34 to 48 minibuses are required during peak hours, whereas, if PUJs are to be considered, 102 units are needed for the service period and 46 to 65 PUJs during peak hours.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- University of the Philippines